Germinated Brown Rice Attenuates Cell Death in Vascular Cognitive Impaired Mice and Glutamate-Induced Toxicity in HT22 Cells - Eve Mon Oo (2020)
Copyright © 2020 American Chemical Society. Germinated brown rice (GBR) with unpolishing, soaking, and germinating processes can improve the texture, flavor, and nutritional value, including GABA and phenolic contents. The effect of GBR was first investigated in vascular cognitive impaired mice and glutamate-induced toxicity in HT22 cells with respect to standard pure GABA. Feeding mice with GBR for 5 weeks showed neuroprotection. In this study, the modified bilateral common carotid artery occlusion mice model was mild but a significant difference in cognitive impairment was still shown. Like pure GABA, GBR decreased cognitive deficits in memory behavioral tests and significantly attenuated hippocampal neuronal cell death at P < 0.001. Similarly to 0.125 μM of GABA, 100 μg/mL of GBR increased HT22 cell viability after glutamate toxicity. GBR affected less apoptotic cell death and less blocking by the GABAA antangonist bicuculline in comparison to GABA. When the results are taken together, the underlying mechanism of GBR protection may mediate though the GABAA receptor and its phenolic contents.